Feature extraction and classification algorithms for assessing muscle condition using multi sensors - Mohamed Sarillee Mohamed @ Mohd Kassim (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2017)
The research objectives are to investigate the relationship between the recorded myograms and muscle fatigue using Pearson Correlation and Linear regression ; to propose and evaluateM-band wavelet transform based feature extraction for extracting salient features from 3 different myograms ; to apply feature level fusion and two stage feature selection for improving the classification of muscle condition (non-fatigue and fatigue).